Water restriction and seed coating in the microbiolization of maize seeds with Trichoderma spp. - Junges, Emanuele; Oliveira Bastos, Bruna; Toebe, Marcos; Muller, Juceli; Cardoso Pedroso, Daniele; Brião Muniz, Marlove Fátima (Comunicata Scientiae, 2014)
The aim of this study was to evaluate the effect of seed microbiolization with Trichoderma spp.techniques associated with water restriction and film coating on the physiological performance ofmaize seed. The treatments were: T1 - Spore suspension: we used the commercial product Agrotrich® plus (0.1 g in 1 ml water/100 seeds), T2 - Water restriction: it was performed on PDA + mannitol (- 0,7 MPa) on which was grown and sporulated Trichoderma spp. disinfected seeds were distributed100 on each plate. When was the first seed root protrusion, the others were removed and dried in alaboratory environment for 48 h, T3 - Pelliculation: performed with the addition of the polymer ColorSeed (50 mL kg-1) to the pesticide treatment containing Trichoderma spp. The seeds were dried for48 h in a laboratory environment. T4 - Water restriction and film coating: after the seeds were primedin the presence of the fungus was made with polymer coverage; T5 - Untreated seeds. The useof water restriction provided efficient microbiolization seeds with Trichoderma spp. with increasedcontrol of fungi. The association of water restriction and film coating provided control of fungi andkept the vigor of maize seedlings. The use of Trichoderma spp. promoted an increase in seedlingvigor of maize, regardless of technique used microbiolization, demonstrating the benefits of thisfungus when applied to corn seeds.